An A.I.-Based Fuzzy Logic DC-DC Converter for USB Type-C Charging - Huang, Can; Wen, Xueyu; Chim, Steve; Ho, Godwin; Tsang, Chi-Chiu; Wu, Andy; Pong, Bryan; Ng, David (2020 IEEE International Conference on Integrated Circuits, Technologies and Applications (ICTA), 2020)
The modernized USB Power delivery (PD)3.0 specification with Type-C interface has become the worldwide fast-charging standard for electronic devices, covering a wide range of use. These power supplies require not only high power delivery but also an intelligent control to monitor the charging processes simultaneously. So, the design of Type-C charger with Digital-Fuzzy PID-control DC-DC Converter is proposed, which gives the optimized performance in Type-C PD charging applications.